Whistleblowing System, Gaya Kepemimpinan, Digitalisasi, Budaya Organisasi dan Fungsi Audit Internal Terhadap Perencanaan Strategis - Gatot Wahyu Nugroho; Nurmala Ahmar (BAJ: Behavioral Accounting Journal, 2022)
This study aims to determine the effect of the Whistleblowing System, Leadership Style, Digitalization, Organizational Culture and Internal Audit Functions on Strategic Planning. This study uses a review of various literatures on Strategic Planning available in various electronic databases. The use of electronic databases is carried out by entering keywords, namely "Whistleblowing System", "Leadership", "Digitalization", "Organizational Culture", "Internal Audit Function", and "Strategic Planning". The results of the literature review show that the Whistleblowing System has an effect on preventing fraud that can hinder the achievement of the strategic plans. Leadership style affects the achievement of strategic plans if the leader is able to motivate his employees. Digitalization is able to help achieve strategic plans by utilizing technology for operational and marketing convenience and accountability. Organizational culture is able to make individuals committed to helping the achievement of strategic plans. The Internal audit function also helps oversee the organization's operations so that strategic planning can be realized.